THE EFFECT OF CATECHINS AND NANOCHITOSAN ON REDUCING BACTERIAL COLONIES AND MATERIAL PERFORMANCE IN PACKAGING FILMS BASED ON PLA/PCL BLEND - Salim, Suryani; Rihayat, Teuku; Fitria; Safitri, Aida (International Journal of Research -GRANTHAALAYAH, 2023)
The extensive utilization of petrochemical polymer-based plastics has led to significant environmental challenges. A viable solution involves the incorporation of high-quality biomaterials as a substitute for traditional plastics. In pursuit of this goal, Polylactic Acid (PLA) and Polycaprolactone (PCL) biopolymers were combined with catechin and nano chitosan additives to innovate food packaging materials. The process involved the utilization of a screw extruder for mixing and melting. The sample formulation employed a combination of PLA polymer (9.5 g) and PCL (0.5 g). The variations in catechin (0%, 5%, 10%, 15%, 20%, 25%, and 30%), while nano chitosan was added in concentrations (5%, 10%, 15%, 20%, 25%, and 30%). The highest tensile strength recorded, at 45.10 MPa, was achieved by sample SA4, as indicated by tensile strength testing, FTIR analysis, and colony reduction. FT-IR analysis revealed the presence of functional groups, namely N-H, C-H, C=O, and C-O, signifying successful interactions between the PLA/PCL matrix blend and the additive components of nanochitosan and catechins. Remarkably, sample SA4 exhibited a remarkable 96% reduction in S. aureus bacterial colonies following 24 hours of storage.